Job Hazard Analyses (JHA) for Ergonomics Risk Factors in Malaysian Pineapple Plantation - Mohamad Salleh, Nur Fazrina; Ezrin Hani, Sukadarin (NIOSH, 2018)
The prevalence of Musculoskeletal Symptoms (MSS) rapidly increases and it is recognized as a significant health outcome in agricultural sector. Agricultural ergonomics risk factor is one of hazards constantly arising from all job task activities including awkward postures and heavy lifting. Job hazard analyses (JHA) were conducted to assess the exposure of ergonomics risk factors in Malaysia Pineapple Plantation. The analyses performed involved two steps. They were: 1) guidelines and manual book Malaysia Pineapple Plantation as references; and 2) conducting walkthrough observation based on checklist approaches at the plantation. The identified risk factors were prolonged exposure of standing, squatting, stooping and kneeling, highly repetitive motion on the lower limbs, deviation and twisting of wrist and lastly, heavy lifting. The analyses confirmed that the exposure to ergonomics risk factors in pineapple plantation is high. It would be desirable to reduce the risk factors by educating and training the pineapple workers to perform their task with strong consideration of occupational safety and health.